Eksistensi Pertunjukan Musik Burdah - Hary Murcahyanto; Yuspianal Imtihan; Mohzana Mohzana; Muhammad Kadafi (Universitas Negeri Medan, 2021)
This paper is based on the results of research aimed at describing the existence and development of Burdah music performances in Lombok Timur The type of research used descriptive qualitatively using methods with the object of study is the Burdah music. The location of this research is in Rempung Village, Pringgasela District, Lombok Timur Regency. The target of the study in this study is the existence of Burdah music performances. Data is collected through observation data collection techniques, interviews and documentation. Data analysis techniques are performed with data reduction steps, data presentation and data verification. The results of this study showed that the factors that support the existence of Burdah music consists of good management, has a complete organizational structure with managerial system, solid in achieving the goal of using an educational system, has a characteristic that maintains a sense of solidarity between members and management and has a lot of performance experience both formal and non-formal. The conclusion of this paper is that the existence of Burdah music is strongly influenced by management factors, solidarity, characteristics and performance experience.